2011
DOI: 10.1038/ejhg.2011.171
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of a deletion region critical for corpus callosal abnormalities in chromosome 1q43–q44

Abstract: Submicroscopic deletions involving chromosome 1q43-q44 result in cognitive impairment, microcephaly, growth restriction, dysmorphic features, and variable involvement of other organ systems. A consistently observed feature in patients with this deletion are the corpus callosal abnormalities (CCAs), ranging from thinning and hypoplasia to complete agenesis. Previous studies attempting to delineate the critical region for CCAs have yielded inconsistent results. We conducted a detailed clinical and molecular char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 21 publications
8
54
1
Order By: Relevance
“…The majority (66%) developed seizures. 1, [8][9][10][11][12]15 Incomplete penetrance is a possible explanation for the absence of ACC in this girl, given that the corpus callosum was apparently normal in at least five patients with 1q43q44 microdeletions that included ZBTB18 as described previously. 1,9,12 We note that brainspecific loss of ZBTB18 in mice leads to a small brain phenotype with ACC and cerebellar hypoplasia.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The majority (66%) developed seizures. 1, [8][9][10][11][12]15 Incomplete penetrance is a possible explanation for the absence of ACC in this girl, given that the corpus callosum was apparently normal in at least five patients with 1q43q44 microdeletions that included ZBTB18 as described previously. 1,9,12 We note that brainspecific loss of ZBTB18 in mice leads to a small brain phenotype with ACC and cerebellar hypoplasia.…”
Section: Discussionsupporting
confidence: 59%
“…1, [8][9][10][11][12] Out of 27 patients with deletions distal or proximal (including the AKT3 gene) to ZBTB18, only 5 (19%) showed corpus callosum abnormalities and 10 (37%) had microcephaly, compared with 82 and 97%, respectively, of patients with deletions including ZBTB18. 1, [8][9][10][11][12] Furthermore, IUGR was seen in 3 out of 14 of these patients (21%) and postnatal growth retardation was seen in 7 out of 23 patients (30%). Collectively, these results support a crucial role for ZBTB18, but with contributions to the phenotype of other genes in patients with larger deletions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,12,14,15 Now, precise genotype-phenotype correlation has been evaluated through the accumulation of patients with variable deletion sizes, and a minimal essential region has been proposed for expressing the main characteristics of 1q44 deletion syndrome. 7,8,[14][15][16] Ballif et al 17 evaluated 22 patients with small interstitial deletions of 1q44 and demonstrated critical regions for microcephaly, ACC and seizures. Consequently, AKT3 was reported to be the gene responsible for microcephaly; zinc finger protein 238 gene (ZNF238) for ACC; and heterogeneous nuclear ribonucleoprotein U gene (HNRNPU) for seizures 17 ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies have investigated the critical region for 1q44 subtelomeric deletion syndrome and found that the core phenotypic features of 1q44 subtelomeric deletion syndrome are microcephaly, abnormalities of the corpus callosum (ACC) and seizures. [4][5][6][7][8][9][10][11][12][13][14][15][16] Recently, Ballif et al 17 analyzed patients with microdeletions of 1q44 and proposed certain genes that may be responsible for individual features.…”
Section: Introductionmentioning
confidence: 99%